2016
DOI: 10.14302/issn.2374-9431.jbd-16-939
|View full text |Cite
|
Sign up to set email alerts
|

Association Of Risk Factors In Gestational Diabetes Mellitus Among Pregnant Mothers Attending At A Tertiary Care Hospital In Bangladesh

Abstract: Objective: To observe association of risk factors with gestational diabetes mellitus (GDM) in a tertiary care hospital of Bangladesh. Materials and methods: Risk factors of GDM were evaluated in pregnant subjects (n=385; age: 26.4±4.9 yrs; body mass index, BMI: 25.3±4.3 kg/m 2 ; mean ± SD) screened by 75 gram oral glucose tolerance test (OGTT) following WHO 1999 criterion irrespective of gestational age in the Department of Endocrinology, Bangabandhu Sheikh Mujib Medical University (BSMMU). BMI, maternal age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Our study indicates that one third of pregnant women have GDM, a rate that is 3–4 times higher than most of the previous studies in Bangladesh. The prevalence of GDM in previous studies ranged between 7% and 14%, except the study that was conducted with women visiting antenatal clinics in an urban tertiary hospital, which reported a prevalence of 40.3% as per the WHO (1999) criteria [ 9 , 10 , 11 , 12 , 13 , 23 ]. The prevalence reported in this study is also three times higher than the pooled overall prevalence of GDM reported in South Asian countries (Bangladesh, India, and Sri Lanka) (11.4%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study indicates that one third of pregnant women have GDM, a rate that is 3–4 times higher than most of the previous studies in Bangladesh. The prevalence of GDM in previous studies ranged between 7% and 14%, except the study that was conducted with women visiting antenatal clinics in an urban tertiary hospital, which reported a prevalence of 40.3% as per the WHO (1999) criteria [ 9 , 10 , 11 , 12 , 13 , 23 ]. The prevalence reported in this study is also three times higher than the pooled overall prevalence of GDM reported in South Asian countries (Bangladesh, India, and Sri Lanka) (11.4%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the prevalence of GDM in Bangladesh, and most relied on the WHO (1999) criteria. The reported prevalence of GDM in these studies, largely from clinic or hospital settings, ranged between 6.8% and 40.3% [ 9 , 10 , 11 , 12 , 13 ]. The most recent estimate of GDM prevalence in Bangladesh is almost a decade old, and the prevalence was 9.7%, according to the WHO (1999) criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Author details 1 Molecular Biotechnology Division, National Institute of Biotechnology (NIB), Ganakbari, Ashulia, Savar, Dhaka 1349, Bangladesh. 2 Department of Endocrinology and Metabolism, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. 3 Department of Biochemistry and Molecular Biology, University of Dhaka, Dhaka, Bangladesh.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…This complication (GDM) is rising rapidly in the prevalence of 36.6% of total pregnancies in Bangladesh [2,3]. This prevalence varies from 0.7 to 51% in Asia [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%